Erlotinib and bevacizumab versus cisplatin, gemcitabine and bevacizumab in unselected nonsquamous nonsmall cell lung cancer - Thomas, Michael; Villalobos Bollen, Matthias Americo; Reinmuth, Niels; Penzel, Roland; Schnabel, Philipp Albert (The European respiratory journal, 2015)
Erlotinib with bevacizumab showed promising activity in recurrent nonsquamous (NS) nonsmall cell lung cancer (NSCLC). The INNOVATIONS study was designed to assess in first-line treatment of unselected cisplatin-eligible patients this combination compared to cisplatin, gemcitabine and bevacizumab. Stage IIIB/IV patients with NS-NSCLC were randomised on erlotinib (150 mg daily) and bevacizumab (15 mg·kg−1 on day 1, every 3 weeks) (EB) until progression, or cisplatin (80 mg·m−2 on day 1, every 3 weeks) and gemcitabine (1250 mg·m−2 on days 1 and 8, every 3 weeks) up to six cycles and bevacizumab (15 mg·kg−1 on day 1, every 3 weeks) (PGB) until progression. 224 patients were randomised (EB n=111, PGB n=113). The response rate (12% versus 36%; p<0.0001), progression-free survival (median 3.5 versus 6.9 months; hazard ratio (HR) 1.85, 95% CI 1.39-2.45; p<0.0001) and overall survival (median 12.6 versus 17.8 months; HR 1.41, 95% CI 1.01-1.97; p=0.04) clearly favoured PGB. In patients with epidermal growth factor receptor mutations (n=32), response rate, progression-free survival and overall survival were not superior with EB. Platinum-based combination chemotherapy remains the standard of care in first-line treatment of unselected NS-NSCLC. Molecular targeted approaches strongly mandate appropriate testing and patient selection. Platinum-based combination chemotherapy remains the standard of care in first-line treatment of unselected NS-NSCLC http://ow.ly/ITkNj